THE INFLUENCE OF THE ROLE OF MIDWIVES ON YOUTH ACTIVENESS IN PARTICIPATING IN YOUTH POSYANDU - Eri Puji Kumalasari; Devy Putri Nursanti (Journal for Quality in Women's Health, 2022)
Background:Adolescents experience many challenges both from themselves or the environment this is a period of storm or stress in adolescents. The purpose of this study was to determine the effect of the role of midwives on youth activity in participating in youth posyandu. Methods: Literature review is done by searching for journals from databases, namely PubMed, Google Scholar. The keywords used are midwives, youth, youth posyandu. Literature that meets the inclusion criteria of 8 journals. Results: This literature review research half 50% using the total sampling technique with most of the 62.5% using a questionnaire sheet, the research analysis is very small using the chi square test of 25%. Conclusion: With the role of midwives on adolescent activity increasing, it was found that there was an influence of the role of midwives on adolescent activity.